2016
DOI: 10.1590/1678-4685-gmb-2015-0126
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium, SNP frequency change due to selection, and association mapping in popcorn chromosome regions containing QTLs for quality traits

Abstract: The objectives of this study were to assess linkage disequilibrium (LD) and selection-induced changes in single nucleotide polymorphism (SNP) frequency, and to perform association mapping in popcorn chromosome regions containing quantitative trait loci (QTLs) for quality traits. Seven tropical and two temperate popcorn populations were genotyped for 96 SNPs chosen in chromosome regions containing QTLs for quality traits. The populations were phenotyped for expansion volume, 100-kernel weight, kernel sphericity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…The LD of Chr 3 and 7 decayed faster than the other chromosomes, with~2.2 kb for a cut-off value of r 2 = 0.11. Past studies have found that this LD pattern (i.e., rapid decay with increasing physical distance) is typical in tropical maize germplasms [6,9,32]. The LD decay pattern in this study was similar to the findings of Yan et al [33] and Coan et al [6], who reported that the LD pattern (in tropical maize germplasms) decreases rapidly in the range of 0.1-10 kb.…”
Section: Linkage Disequilibriumsupporting
confidence: 90%
“…The LD of Chr 3 and 7 decayed faster than the other chromosomes, with~2.2 kb for a cut-off value of r 2 = 0.11. Past studies have found that this LD pattern (i.e., rapid decay with increasing physical distance) is typical in tropical maize germplasms [6,9,32]. The LD decay pattern in this study was similar to the findings of Yan et al [33] and Coan et al [6], who reported that the LD pattern (in tropical maize germplasms) decreases rapidly in the range of 0.1-10 kb.…”
Section: Linkage Disequilibriumsupporting
confidence: 90%
“…Regardless of the uncertainty of their function, class II TPSs show strict developmental and tissue specific gene regulation, strong diurnal regulation, and sensitivity to a variety of abiotic stressors [ 39 , 74 , 77 ]. The maize ZmTPSII.3.3 gene was shown to associate with the kernel expansion trait in popcorn [ 78 ]. The class II TPS proteins 5, 6 and 7 from Arabidopsis were found to be phosphoproteins and bind to 14–3-3 proteins when phosphorylated at Ser22 and Thr49 [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Association studies have been successfully used to identify the genetic basis of quantitative traits, allowing not only the identification of quantitative trait loci (QTLs), but also the identification of candidate genes based on statistical significant differences between markers and phenotypes [3]. Single nucleotide polymorphism (SNP) markers contributed to expand the knowledge of the genetic structure and diversity of maize populations.…”
Section: Introductionmentioning
confidence: 99%
“…Association mapping was successfully applied in maize to identify genomic regions related to plant height [4], root development [10], resistance to Fusarium graminearum Schwabe [11], and oil biosynthesis in maize kernels [9]. Mapping the associations of chromosomal regions of popcorn kernels revealed the candidate genes for starch, storage protein, pericarp polysaccharide, and oil grain contents in this maize variety [3]. However, little is known about the genes involved in the control of the main popcorn agronomic traits such as grain yield and popping expansion.…”
Section: Introductionmentioning
confidence: 99%